Pelayanan Prima Sebagai Upaya Pelaksanaan Good Government - Achnes, Sofia (Universitas Riau, 2011)
One impact is most felt by the government in the era of globalization, the 21st Century, and publicadministration reform, the public demands to improve the quality of service received from the government. Inother words, people get “excellent service” from the government. Community demands are not excessive,therefore during this “paradigm to serve” from the government bureaucracy, in fact, reverse the “paradigmserved”. Although many critics and even blasphemy against the slow pace of public service provided thegovernment bureaucracy, but it seems not much significant change. The slowness of service, based onobservations and assessments of experts, among others, as a result of the path length that must be taken to anactivity (work procedures convoluted), deviant attitudes and behavior of government bureaucracy, weaksupervision immediate superior, systems and management style tend to be authoritarian, centralized authorityand power, professionalism, limited facilities and infrastructure, as well as other things. The question thatthen arises is how the efforts of the government, so that the service provided to the community is increasing itsquality. This is important, therefore, the public has a right to get excellent service from the government. Atleast three criteria for excellent service quality measures, namely: “faster, better, and cheaper”, a highlycoveted community. Associated with these things, the following will be presented on “Excellent Service”.